The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acsanm.3c02443
|View full text |Cite
|
Sign up to set email alerts
|

ZIF-8/Curcumin-Loaded Electrospun Nanofiber Membrane for Wound Healing

Chen Hang,
Zhou Wei,
Xiang Jieyu
et al.

Abstract: Conventional clinical dressings have limited antibacterial, anti-inflammatory, and antioxidant activities and are unable to maintain moisture in wounds. To overcome the aforementioned limitations of conventional medical materials, it is urgent to develop multifunctional materials that can accelerate wound healing in clinical practice. In this study, a composite of polycaprolactone (PCL) and curcumin-incorporated zeolitic imidazolate framework-8 (denoted as PCL/ZIF-8/CUR) was prepared by using a seed-free soaki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The water contact angle results revealed that incorporation of drug-loaded MOFs throughout the polycaprolactone significantly improved hydrophilicity stemming from the high content of hydroxyl groups on the MOF nanoparticles which increased polarity of the polymer matrix. [174] Zinc imidazolate frameworks were grown into chitin sponges in situ to yield an effective hemostasis and antibacterial wound dressing. The nanocrystals were not only distributed homogenously all over the sponge, but also got anchored firmly on the sponge (Figure 13).…”
Section: Enhanced Moisture Management With Mofsmentioning
confidence: 99%
“…The water contact angle results revealed that incorporation of drug-loaded MOFs throughout the polycaprolactone significantly improved hydrophilicity stemming from the high content of hydroxyl groups on the MOF nanoparticles which increased polarity of the polymer matrix. [174] Zinc imidazolate frameworks were grown into chitin sponges in situ to yield an effective hemostasis and antibacterial wound dressing. The nanocrystals were not only distributed homogenously all over the sponge, but also got anchored firmly on the sponge (Figure 13).…”
Section: Enhanced Moisture Management With Mofsmentioning
confidence: 99%